THE RELATIONSHIP BETWEEN ECONOMY AND CRIME IN THE COVID-19 PANDEMIC ERA (CASE STUDY OF INDIA AND INDONESIA) - Rajas Kumar (CV. Tirta Pustaka Press, 2024)
The economic determination of criminology according to Karl Marx is influenced by economic pressure, to fight crime rates, it must be accompanied by economic improvement. Crime rates are seen as a result or as a result of economic conditions which are considered to have a causal relationship. The research method used is qualitative by trying to present social phenomena that occur in the society of the two countries (India and Indonesia). The data collection technique used is a literature review by collecting data from books and journals that can be accessed online. Data analysis is carried out in depth and described qualitatively. The results of this research showed that this pandemic has also made India's economy collapse. Many companies have fired staff, and the informal sector was also in crisis. Experts say that rising unemployment during the Corona crisis can encourage many people to commit crimes, especially young people. The most frequent crime in Indonesia due to economic problems is theft. Theft is currently a threat to most communities. Theft is a complex social problem that is influenced by various factors, including economic factors, lack of security systems, limited supervision, drug abuse, and limited opportunities.